THE IMPLEMENTATION OF MOBILE VIDEO TASK TECHNIQUE IN TEACHING SPEAKING AT THE ELEVENTH GRADE STUDENTS OF SMKN 1 KEMPO - Elvira Trisna Fadillah; Ratna Dewi; Ilmiah (Journal of Language Testing and Assessment, 2021)
The aimed of this research was to find out the improve of students’ speaking ability by using Mobile Video Task that focused on students’ fluency at the Eleventh Grade of SMKN 1 Kempo. The researcher used Pre-experimental Design with one group pre-test and post-test, and data collection based on the test. The sample of this research was class XI which consisted of 20 students. The sample was taken by using Purposive Sampling Technique. The research findings showed that the students’ difference before and after using mobile video task was significantly different. The students’ pre-test mean score in term of fluency was 65.15 to be 75.45 in post-test. Based on the findings, it can be concluded that mobile video task technique was effective to improve the speaking ability of the students at the Eleventh Grade of SMKN1 Kempo in the Academic Year 2020/2021.